Understanding the spatiotemporal recruitment dynamics of commercially important fish species in the North Sea - Akimova, Anna (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2017)
Nearly 75% of marine fish stocks are overexploited and management based on sound science is needed to promote stock recovery and sustainability. Understanding recruitment, the number of fish entering the fishable stock every year, is key to sustainable management strategies. This thesis addressed the need for investigation of the spatial and temporal variability of the processes driving recruitment variability of commercially important fish species in the North Sea. In Chapter 4, a solid basis for analyses of the spatial and temporal variability of North Sea hydrography was produced. A physical-statistical model (Adjusted Hydrography Optimal Interpolation, AHOI) was developed to produce gridded hydrography based on available oceanographic observations. The AHOI was applied to produce high-resolution (0.2° x 0.2°) monthly maps of temperature and salinity in the North Sea for the period between 1948 and 2013. The accuracy of 0.3 °C for temperature and 0.1 for salinity maps was assessed. The AHOI dataset was made freely available for the scientific community to promote its use in ecosystem-related studies. In Chapter 5, the AHOI maps were used to explore how the environment influences the biomass and reproduction of nine commercially important fish species in the North Sea. The stocks examined were: Atlantic cod (Gadus morhua), Atlantic herring (Clupea harengus), European sprat (Sprattus sprattus), European plaice (Pleuronectes platessa), haddock (Melanogrammus aeglefinus), Norway Pout (Trisopterus esmarkii), whiting (Merlangius merlangus), common sole (Solea solea), and saithe (Pollachius virens). Spatially-explicit cross-correlation analysis revealed a positive correlation between water temperature in the north-western North Sea and herring spawning stock biomass, and a negative correlation between temperature in the southern North Sea and the pre-recruitment survival index of sole. A positive correlation was found between water salinity and the spawning stock biomass and recruitment of sprat. Moreover, the ...